Aktualisasi Nilai-Nilai Ahlussunnah wal Jamaah Masyarakat Kampung Sumber Makmur - Pangeran, Giman Bagus; Subiantoro, Subiantoro; Rohman, Nur; Sutekno, Rendi (Tapis: Jurnal Penelitian Ilmiah, 2022)
Ahlus Sunnah Wal Jamaah (aswaja) Nahdlatul Ulama (NU) is one of the sects that are mostly followed by the people of Sumber Makmur Village. There are so many aswaja NU's teachings that have become routine and have even become a culture attached to the people of Sumber Makmur Village. Aswaja NU's sect is also a stronghold for the entry of sects that bring radical ideas out of Islamic values. One of the methods used by aswaja NU in actualizing the values ​​of Islamic practice is to provide an understanding to the public about the importance of studying the laws used in worship, both related to God and the environment. The educational method used by aswaja NU to convey learning to the Sumber Makmur society is adopted from formal education theory combined with da'wah methods in Islamic boarding schools.